Adultyzm – uprzedzenia przeciwko młodym ludziom - Jankowiak, Barbara (Studia Edukacyjne, 2020)
The article analyses adultism, or prejudice against children and young people as singled out of ageism, i.e. prejudice on grounds of age. Adultism involves a stereotypical perception of and approach to younger members of the society solely because they are young. Scientifictheories on young people and adolescence have transformed from those stressing the negative features of teenagers themselves and seeing adolescence as the “most difficult”development stage to those which highlight the potential of young people and the coming-of-age period as one of many equally important stages of life. Analysis of relevant literature and studies indicates that there is a need to fillthe gap both in the theoretical approach to adultism and in studies of prejudice against young people.